The effect of investment understanding, risk perception, income, and investment experience on investment behavior on capital market investors in Klaten District - Kurniawati, Rizka; Suparlinah, Irianing; Farida , Yusriyati Nur (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of investment understanding, risk perception, income, and investment experience on behavior of capital market investors in Klaten Regency. This study uses the population of Klaten Regency who are stock investors and already have income. Data was collected by distributing questionnaires to the respondents and using purposive sampling method for sampling. The data obtained in this study were 96 respondents. This study have result that investment understanding and income have a positive effect on investment behavior of capital market investors. Risk perception and investment experience have no effect on investment behavior of capital market investors. As an implication, investors need to have a good understanding of investment so that they can easily and correctly make investment decisions. The community has started to allocate income for investment, but it needs to be supported by knowledge and good financial planning.